The Impact of Personalized Guest Experiences on Customer Loyalty in the Hotels of Kolkata - Bharadwaj, Anindita; Bathla, Gaurav (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
This study explores the impact of personalized guest  experiences on customer loyalty in hotels located  in Kolkata, India. In today’s competitive hospitality  landscape, customer loyalty is increasingly influenced by  tailored services that cater to individual guest preferences.  The research is grounded in the understanding that  personalized experiences including customized services,  communication, and attention to guest-specific needs can  significantly enhance guest satisfaction and foster long term loyalty. The objectives of the study are threefold: to  examine the demographic profile of guests visiting Kolkata’s  hotels, to identify key factors influencing customer loyalty  through personalization and to analyse the extent to which  personalized guest experiences impact loyalty outcomes.  A quantitative research design was adopted using a  structured questionnaire as the primary data collection  tool. The survey was distributed among hotel guests  in Kolkata using convenience sampling, yielding 212  valid responses. Responses were measured on a 5-point  Likert scale and analysed through descriptive statistics,  factor analysis, and ANOVA. The findings reveal that  personalized guest experiences such as tailored services,
Keywords: Personalized guest experiences; customer loyalty; hospitality industry; demographic factors; competitive advantage